A Robust Multi‐Objective Pressure Sensor Placement Method for Burst Detection in Water Distribution Systems - Du, Kun; Yu, Jinxin; Zheng, Feifei; Xu, Wei; Savic, Dragan; Kapelan, Zoran (Water resources research, 2024)
Bursts in water distribution systems (WDSs) lead to water wastage and negative environmental impacts. Optimizing pressure sensor placement (PSP) for effective burst detection is crucial for prompt response and adverse event mitigation. While many optimization methods are available for this purpose, their resulting PSP strategies often exhibit large variability caused by background noise or metering accuracy, representing low robustness. This consequently hinders the wide application of existing PSP methods for burst detection in WDSs. This study proposes a novel multi‐objective PSP method aimed at maximizing burst detection while minimizing the number of sensors. Within this method, a new threshold metric is introduced to quantify the minimum detectable burst outflow across all pipes. The metric has the key advantage of taking into account the fact that the relative magnitude of the detectable threshold for different pipes is independent of noise, thereby addressing the low robustness issue. The proposed method is applied to three WDSs, and results show that it can consistently achieve robust optimal PSP strategies across diverse noise conditions. Comprehensive comparisons between the proposed method and the other benchmark approaches are conducted using five metrics, including detection performance and layout characteristics. These comparisons reveal the properties of each optimization method and show how detection performance is affected by various placement features. It is anticipated that the proposed method can be useful in engineering practice due to its great robustness in determining the optimal PSP strategies for burst detection in WDSs compared to other alternatives. Plain Language Summary In water distribution systems (WDSs), bursts can cause water wastage and environmental harm. Strategic pressure sensor placement (PSP) is crucial for prompt burst detection and mitigation. However, existing PSP methods often lack robustness due to background noise or metering inaccuracies, hindering their widespread use. This study introduces a novel multi‐objective PSP method aiming to maximize burst detection while minimizing sensor count. It includes a new threshold metric to quantify minimum detectable burst outflow, independent of noise, addressing the robustness issue. Based on results from three case studies, the proposed method consistently achieves optimal PSP strategies across diverse noise conditions. Comparative analyses with benchmark approaches demonstrate its robustness and effectiveness in detecting bursts. This method can be very useful in engineering as it can provide reliable PSP strategies for WDS burst detection. Key Points The proposed method deals with issues of low robustness and inconsistency within pressure sensor placements Five metrics and three case studies are used for comparison between the proposed method and three existing approaches Placements with a larger average shortest‐path distance outperform those with an average geographic‐plane distance in detection performance